Mapping bacterial diversity and metabolic functionality of the human respiratory tract microbiome. Issue 1 (31st December 2022) - Mancabelli, Leonardo; Milani, Christian; Fontana, Federico; Lugli, Gabriele Andrea; Tarracchini, Chiara; Turroni, Francesca; van Sinderen, Douwe; Ventura, Marco
ABSTRACT: Background: The Human Respiratory Tract (HRT) is colonized by various microbial taxa, known as HRT microbiota, in a manner that is indicative of mutualistic interaction between such microorganisms and their host. Aim: To investigate the microbial composition of the HRT and its possible correlation with the different compartments of the respiratory tract. Methods: In the current study, we performed an in-depth meta‐analysis of 849 HRT samples from public shotgun metagenomic datasets obtained through several distinct collection methods. Results: The statistical robustness provided by this meta-analysis allowed the identification of 13 possible HRT-specific Community State Types (CSTs), which appear to be specific to each anatomical region of the respiratory tract. Furthermore, functional characterization of the metagenomic datasets revealed specific microbial metabolic features correlating with the different compartments of the respiratory tract. Conclusion: The meta-analysis here performed suggested that the variable presence of certain bacterial species seems to be linked to a location-related abundance gradient in the HRT and seems to be characterized by a specific microbial metabolic capability.